On the elaboration of the method of accelerated rearing of salmon fry up to their smoltification - Malikova, E.M. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1967)
A method for increasing of the growth rate and the viability of salmon Salmo salar fry is described. The enrichment of the artificial feed with biologically active growth stimulators - the trace elements and the substances containing antibacterial compounds and phytoncides, is considered. The results of the experiments on the rearing of the 0-group salmon with different feeds are presented. The investigation allows a more precise definition of the ingredients in the artificial feed KRT that is used for salmon rearing in Latvia. Published Not Known